ISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KENDARAAN DALAM MENDISTRIBUSIKAN ZAKAT, INFAK DAN SEDEKAH - Emi Suryadi (Universitas Raharja, 2016)
Decision support systems into a solution in deciding the problem of various election BAZNAS vehicles in the city of Mataram. Various types of vehicles available in the office BAZNAS Mataram, this can help in the process of decision-support of various criteria and the selected alternative. The results of data collection and calculation processes Analytic Hierarchy Process (AHP) to get the value on which to base recommendations for the selection of vehicles in the city of Mataram BAZNAS namely deer with a total value of 0.4998097. The highest value is the value of the selected vehicle that can be used in distributing Zakat, Infak and Sedekah to various areas in the city of Mataram. The result of this decision in accordance with the calculation criteria and alternatives on which to base the selection of vehicles in the city of Mataram BAZNAS Office in choosing a vehicle. Zakat, Infakand Sedekah distributed to the poor are earning less than the average and for the people of the poor and orphans so that it can be utilized for the welfare of society, especially in the city of Mataram.